Issues Of Legal Regulation Of Open Meetings In Uzbekistan (Zien Journal of Social Sciences and Humanities, 2025)
This article investigates the organizational and legal framework governing the attendance of individuals and legal entities (information users) and the participation of public control subjects in open collegial meetings of state bodies (hereinafter referred to as "open meetings"). The study revealed that the legislation only regulates the attendance of information users at open meetings of ministerial collegiums and other government bodies, as well as open meetings of certain local executive bodies (khokimiyats). At the same time, the legislation does not take into account the holding of online meetings and contains other shortcomings. A hypothesis was put forward that to eliminate the existing shortcomings, it is necessary to define the concept of "open collegial meeting of a state body," to correctly use the words "attendance" and "participation." The results of studying the norms of national legislation, controversial terms, and the experience of foreign countries confirmed the hypothesis. The author's definition of this concept made it possible to objectively outline the content and types of open meetings of state bodies, regulate the attendance and participation of citizens in them, and develop proposals for holding online open meetings